2010
DOI: 10.1186/1475-2875-9-115
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in Brazil: an overview

Abstract: Malaria is still a major public health problem in Brazil, with approximately 306 000 registered cases in 2009, but it is estimated that in the early 1940s, around six million cases of malaria occurred each year. As a result of the fight against the disease, the number of malaria cases decreased over the years and the smallest numbers of cases to-date were recorded in the 1960s. From the mid-1960s onwards, Brazil underwent a rapid and disorganized settlement process in the Amazon and this migratory movement led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
415
0
72

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 404 publications
(492 citation statements)
references
References 70 publications
5
415
0
72
Order By: Relevance
“…In Brazil, P. falciparum predominated with more than 50% of the cases from 1966 to 1973 and from 1984 to 1988, which is attributed to the accelerated migration, expansion of mining activities, deforestation and settlement projects 12,20,33 . P. vivax began to predominate after 1988, starting from 48.6% 20 to over 83.7% nowadays 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brazil, P. falciparum predominated with more than 50% of the cases from 1966 to 1973 and from 1984 to 1988, which is attributed to the accelerated migration, expansion of mining activities, deforestation and settlement projects 12,20,33 . P. vivax began to predominate after 1988, starting from 48.6% 20 to over 83.7% nowadays 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the most frequent species that cause infection in humans are: P. vivax, which accounted for 83.7% of registered cases, P. falciparum, by 16.3% and P. malariae (rarely observed) 26 . However, studies conducted by ARRUDA et al 2 revealed a discrepancy between the prevalence of antibodies against P. malariae and the malaria cases officially reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As espécies que causam malária no Brasil são Plasmodium vivax -que responde por cerca de 85% dos casos registrados, P. falciparum -que causa aproximadamente de 15% deles, e P. malariae -responsável por uma diminuta percentagem dos casos 2,3,24 . Não há transmissão de P. ovale no Brasil, e os poucos registros são importados de países africanos 7 .…”
Section: Discussionunclassified
“…Both P. falciparum and P. vivax are still transmitted across the Amazon Basin, with rare Plasmodium malariae infections. However, P. vivax now causes 85% of the 315,000 malaria cases reported in this country each year (Oliveira-Ferreira et al 2010), suggesting that this species may be less susceptible to the malaria control strategies currently used in Brazil.…”
mentioning
confidence: 99%